(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The cultural heritage of Prai Ijing Traditional Village in West Sumba embodies local identity through its distinctive architectural traditions. However, the preservation of this architecture faces significant challenges due to modernization, climate change, and fire hazards. Devastating fires, such as those in Tarung Village, Bodo Maroto, and several other villages, have led to the destruction of cultural heritage, resulting in both material losses and profound cultural impacts. This study aims to develop a community-based fire mitigation strategy to safeguard Sumbanese architecture. Employing a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. The findings highlight the critical role of social capital, particularly the kabizzu rule, in fire mitigation efforts. Additionally, traditional spatial and material planning, along with Wulla Poddu practices, serve as inherent fire mitigation measures. By integrating local knowledge with community-based risk management, the novelty of this study is to propose a comprehensive strategy in order to enhance fire resilience while preserving cultural heritage. Effective fire mitigation requires a comprehensive approach encompassing education, community training, and the adaptation of fire-resistant building materials to strengthen community resilience and ensure the sustainability of Sumbanese architecture for future generations.